Unraveling the causal impact of smoking and its DNA methylation signatures on cardiovascular disease: Mendelian randomization and colocalization analysis - Si Cao; Youjie Zeng; Ke Pang; Minghua Chen; Ren Guo; Nayiyuan Wu; Chao Fang; Huiyin Deng; Xiaoyi Zhang; Xiaohui Xie; Wen Ouyang; Heng Yang (Clinical Epigenetics)
Abstract Background To explore the mechanisms linking smoking to cardiovascular diseases (CVDs) from an epigenetic perspective. Methods Mendelian Randomization (MR) analysis was performed to assess the causal effects of smoking behavior and DNA methylation levels at smoking-related CpG sites on nine CVDs, including aortic aneurysm, atrial fibrillation, coronary atherosclerosis, coronary heart disease, heart failure, intracerebral hemorrhage, ischemic stroke, myocardial infarction, subarachnoid hemorrhage. Colocalization analysis was used to further identify key smoking-related CpG sites from the MR causal estimates. Reactome enrichment analysis was used to elucidate the potential mechanisms. Results MR analysis indicates that smoking behaviors are significantly associated with an increased risk of nine CVDs (OR > 1, P < 0.05). Through MR and colocalization analysis, five key smoking-related CpG sites were ultimately determined. DNA methylation alteration at cg25313468 (located in the TSS1500 region of REST) is simultaneously associated with the risk of atrial fibrillation, coronary atherosclerosis, coronary heart disease, and myocardial infarction. Additionally, cg21647257 (located in the TSS200 region of CLIP3) is associated with the risk of atrial fibrillation; cg06197751 (located in SGEF gene body) and cg07520810 (located in ARID5B gene body) are associated with the risk of coronary atherosclerosis; cg16822035 (located in MCF2L gene body) is associated with the risk of myocardial infarction. Enrichment analysis suggests that phosphatase and tensin homologue (PTEN) may be involved in the downstream mechanisms of cg25313468 (REST). Conclusion This study uncovers the relationship between smoking, DNA methylation, and CVDs, providing new insights into the pathogenic effect of smoking on CVDs from an epigenetic perspective.